2016
DOI: 10.1097/sla.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Intraoperative Ventilation Strategies to Prevent Pulmonary Complications

Abstract: Intraoperative LTV ventilation in conjunction with PEEP and intermittent recruitment maneuvers is associated with significantly improved clinical pulmonary outcomes and reduction in length of hospital stay in otherwise healthy patients undergoing general surgery. Providers should consider application of all the 3 elements for a comprehensive protective ventilation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 35 publications
3
66
1
Order By: Relevance
“…8 mL/kg predicted bodyweight). This is in line with current recommendations [25][26][27] and is used in previous clinical trials of intraoperative ventilation before [12,13,15], allowing for good comparison of the DESIGNATION results with those from preceding trials.…”
Section: Discussionsupporting
confidence: 77%
“…8 mL/kg predicted bodyweight). This is in line with current recommendations [25][26][27] and is used in previous clinical trials of intraoperative ventilation before [12,13,15], allowing for good comparison of the DESIGNATION results with those from preceding trials.…”
Section: Discussionsupporting
confidence: 77%
“…Pulmonary ventilation, controlled by volume rather than pressure, might modify the rate of postoperative pulmonary complications, even though studies in patients with acute lung injury have not shown significant differences . Postoperative pulmonary complications are associated with intra‐operative PEEP, ventilatory driving pressure and oxygen partial pressure . Studies have reported effects of pressure‐controlled vs. volume‐controlled intra‐operative ventilation on physiological variables but not clinical pulmonary outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from pressure control ventilation, volume‐control ventilation and PEEP, the final component to the methodology involved alveolar recruitment. There are many methods described in the literature relating to alveolar recruitment . Amato et al.…”
Section: Discussionmentioning
confidence: 99%